Anxiety Management During the Covid-19 Pandemic - Muhammad Anwari (UMBanjarmasin, 2021)
Coronavirus disease 2019 or also known as COVID-19 is currently a pandemic in almost all countries in the world. According to the World Health Organization (WHO) on April 6, 2020, the number of sufferers in the world was 1,278,523 infected with Covid-19 cases. Coronavirus disease 2019 or also known as COVID-19 is currently a pandemic in almost all countries in the world. This pandemic outbreak has a negative impact on the physical and psychological health of individuals and society. In line with this, the people in Karang Bunga Mandastana Village feel anxious by the state of the spread of the Covid-19 virus, it is necessary to take good care of this anxiety. In the form of providing the right information in overcoming the anxiety experienced by the people in the Karang Bunga Mandastana Village. One way to overcome anxiety is by breathing relaxation techniques, breathing relaxation is a breathing exercise with slow and deep breathing techniques, using the diaphragm muscle, thus allowing the abdomen to be lifted slowly and the chest to be fully expanded. This breathing relaxation has been proven to be one of the treatment methods in overcoming anxiety.